Enfermedad renal crónica: Potasio y su dieta - Ashley R. Kendall; Nancy J. Gal; Wendy J. Dahl (EDIS)
This is a Spanish language translation of FSHN16-9/FS287: Chronic Kidney Disease: Potassium and Your Diet